Congenital infiltrating lipomatosis of the face: A case report with review of literature - Deepa D'souza; G Subhas Babu; Shishir Ram Shetty; Vinay Rasquinha (Wolters Kluwer Medknow Publications, 2014)
Congenital infiltrating lipomatosis of the face (CIL-F) has been described as a disorder in which mature lipocytes invade adjacent tissues in the facial region. Its etiology and pathogenesis is unknown. The tumor is congenital in origin and occurs in infancy or early childhood. It is unencapsulated and characterized by diffuse infiltration of mature adipose tissue over normal muscle fibers, rapid growth, associated osseous hyperplasia, and a high recurrence rate postsurgical intervention. Due to its diffuse infiltration and involvement of important facial structures, complete surgical excision is often impossible. CIL-F is rare and there are only a few cases reported in the available literature. We present the case of a 17-year-old female, who reported with the complaint of recurrent unilateral facial swelling, with a history of two previous resections.